Voices/Voces in the Borderlands: A Colloquy on Re/constructing Identities in Re/constructed Legal Spaces - Harrison, Melissa; Montoya, Margaret E. (Columbia Journal of Gender and Law, 1996)
While derided as the bane of the Western intellectual tradition and a threat to the most noble of human achievements, multiculturalism (or postmodernism dressed in grunge) has settled with a shrug into the pages of the Spiegel catalog. Listen, as we are cajoled that: [I]n a perfect world, it would be out to tell anyone what’s in. In the meantime, a few ideas seemed important to us. Diversity. A home should be as surprising as its owner. Integrity. There’s a reason some things are called classics. Efficiency. If it isn’t smart, it’s stupid. Other than that, our advice is to do what you want. Be who you are. Make yourself at home.